199 COVID-19 Pandemic Sleep and Dreams at the US-Mexico Border. (3rd May 2021) - Isalva, Luz; Valencia, Dora; Ghani, Sadia; Delgadillo, Marcos; Bastien, Célyne; Madhivanan, Purnima; Krupp, Karl; Ruiz, John; Killgore, William; Wills, Chloe; Grandner, Michael
Abstract: Introduction: The impact of the COVID-19 pandemic in the border region is not well-described, including the impact of pandemic-related sleep disturbances on dream experiences, despite frequent reports of meaningful changes to dreams in the population. Methods: Participants were 155 individuals who completed the Nogales Cardiometabolic Health and Sleep (NOCHES) Study and a COVID sub-study (95% Hispanic/Latino). Participants were asked whether, as a result of the pandemic, they have experienced more schedule regularity, improved/worsened sleep, more initial or middle-of-the-night insomnia, more sleepiness, and more napping. They were also asked whether they experienced more, fewer, or the same amount of dreams in general, positive dreams, and negative dreams. Multinomial logistic regressions were used to examine overall, positive, and negative dream recall (more or less vs same) as outcome and perceived change in sleep as independent variable, adjusted for age, sex, socioeconomics, and mental health symptoms (assessed with PHQ4). Results: Those who reported more schedule regularity were less likely to report more negative dreams (Relative Risk Ratio [RRR]=0.40, p=0.010). Those who reported improved sleep were also more likely to report more positive dreams (RRR=3.97, p=0.004). Those with worsened sleep were more likely to report fewer dreams overall (RRR=2.23, p=0.037), fewer positive dreams (RRR=2.24, p=0.003) and more negative dreams (RRR=3.69, p<0.0005). Those with more initial insomnia were more likely to report fewer positive dreams (RRR=2.43, p=0.002) and more negative dreams (RRR=4.12, p<0.0005). Those with more middle-of-the-night insomnia reported fewer dreams overall (RRR=2.35, p=0.018), fewer positive dreams (RRR=2.55, p=0.001), and more negative dreams (RRR=5.01, p<0.0005). Those with more daytime sleepiness were more likely to report fewer dreams overall (RRR=4.75, p<0.0005), fewer positive dreams (RRR=1.92, p=0.019), and more negative dreams (RRR=3.91, p<0.0005), and were less likely to report more positive dreams (RRR=0.26, p=0.018). Those who reported napping more were more likely to report fewer dreams overall (RRR=2.78, p=0.008), fewer positive dreams (RRR=2.10, P=0.008), and more negative dreams (RRR=2.83, p=0.003), and were less likely to report more positive dreams (RRR=0.16, p=0.004). Conclusion: Those whose sleep worsened due to the pandemic reported less dream recall, and dream content that was more negative and less positive overall. Support (if any): R01MD011600, R01DA051321